Rare primary anorectal malignant melanoma presenting with painless hematochezia: a case report - Zhong, Yuchun; Zou, Yueji; Peng, Long; Hu, Xiaoyun; Xu, Wei (Frontiers in Oncology, 2025)
BackgroundAnorectal malignant melanoma (ARMM) is an exceedingly rare and highly aggressive malignancy characterized by low prevalence, high misdiagnosis rates, and frequent recurrence/metastasis.Case reportThis report details the case of a 51-year-old woman presenting with persistent bright red blood in her stool. Digital rectal examination revealed a firm, spherical mass approximately 4 cm from the anal verge. Colonoscopy identified a pedunculated polypoid lesion (~2.5 cm in diameter) near the anorectal junction. Based on clinical symptoms, physical findings, and endoscopic features, a high suspicion of rectal cancer was initially raised. However, subsequent histopathological evaluation of biopsy specimens revealed immunohistochemical positivity for MelanA, S100, and Ki-67 (~30%), suggesting a probable diagnosis of malignant melanoma. After completing preoperative contrast-enhanced abdominal CT and pelvic MRI examinations and excluding surgical contraindications, the patient underwent laparoscopic-assisted abdominoperineal resection (Miles procedure) and postoperative adjuvant therapy with toripalimab. Moreover, no signs of recurrence were found during follow-up over 3 months postoperatively.ConclusionThis case underscores that ARMM can be clinically indistinguishable from rectal carcinoma, posing a high risk of misdiagnosis. It highlights the critical role of histopathology and immunohistochemistry (IHC) in definitive differentiation, emphasizing the necessity of accurate diagnosis through IHC. Finally, it demonstrates the evolving treatment paradigm from extensive surgery toward a multidisciplinary approach integrating radical resection with adjuvant immunotherapy, reflecting advances in molecular insights and ameliorated outcomes.